Analysis of Collaborative Governance in the Implementation of Satu Data Indonesia - Sapto Setiyawan, Luluk; Yusrina, Yusrina; Mubarokah, Sindy Atul; Asropi, Asropi (Jurnal Ilmiah Administrasi Publik, 2025)
The implementation of Satu Data Indonesia (SDI) is currently considered not to have reached the optimal levels of success. The primary focus of the research is on the Analysis of Collaborative Governance theory by Ansell and Gash in the implementation of SDI, with details divided into four sub-chapters of study aspects: (1) starting conditions, (2) facilitative leadership, (3) institutional design, and (4) the collaboration process. The research findings show that at the initial stage, the limitation of roles cause an imbalance of influence and power, which hinders commitment and participation between parties. Facilitative leadership in SDI is considered too narrow and not yet effective. This is due to the limited involvement between SDI sectors, restricted to intergovernmental collaboration without involving the private sector and universities. The institutional design shows that the implementation of SDI has been supported by various regulations. However, in practice, regulatory obstacles still exist in data exchange, especially to individual data, thus it is necessary to strengthening the SDI regulatory framework through legislation.  the involvement of the non-government sector in the collaboration process enhances the role of the private sector and universities in producing and processing data. This reduces the exclusivity of the role that the government has in SDI so that there is a balance of influence and increased participation between parties.